Assessment of groundwater intrinsic vulnerability using GIS-based DRASTIC method in district Karak, Khyber Pakhtunkhwa, Pakistan - Muneer, Muhammad; Khan, Mumtaz Ali; Shinwari, Fayaz Ullah; Ahmed, Ijaz; Siyar, Syed Mamoon; Alshehri, Fahad; Shahab, Muhammad (Frontiers in Water, 2025)
The Study area lies in the southern Kohat deformed fold and thrust belt. This part of the Kohat plateau, borders the southern extension of the Himalayan deformation, with the Salt range to the south most. The research is based on DRASTIC model. Anthropogenic activities have the potential to pollute groundwater. An essential component of managing groundwater is vulnerability mapping. This study used the DRASTIC model to analyze aquifer vulnerability and identify the hydrogeological condition in the southern portion of the Karak, Khyber Pakhtunkhwa. For the models, the information layers were provided via geographic information systems (GIS). The DRASTIC model uses seven environmental parameters. Vulnerability index concentrations were found to be 0.78% for Very Low vulnerability, 9.57% for Low vulnerability, 24.96% for Moderate vulnerability, 54.01% for High vulnerability, and 10.68% for Very High vulnerability, according to the results. A total 164.446 km2 of the total 1,540 km2 area is covered by the Very High vulnerable zone. The highest Nitrate concentration recorded in the area is 11 ppm and lowest is 4.4 ppm. Around 45% of the samples surpassed the approved limit of PSQWA (Pakistan Standards and Quality Control Authority) and NSQWQ (National Standards for Quality of Water) standard. The concentration of Nitrate >10 ppm represent that some human action has contributed toward the highest concentration.